The Linked Fragment: TEI and the Encoding of Text Reuses of Lost Authors - Monica Berti; Bridget Almas; David Dubin; Greta Franzini; Simona Stoyanova; Gregory R. Crane (Journal of the Text Encoding Initiative)
This paper presents a joint project of the Humboldt Chair of Digital Humanities at the University of Leipzig, the Perseus Digital Library at Tufts University, and the Harvard Center for Hellenic Studies to produce a new open series of Greek and Latin fragmentary authors. Such authors are lost and their works are preserved only thanks to quotations and text reuses in later texts. The project is undertaking two tasks: (1) the digitization of paper editions of fragmentary works with links to the source texts from which the fragments have been extracted; (2) the production of born-digital editions of fragmentary works. The ultimate goals are the creation of open, linked, machine-actionable texts for the study and advancement of the field of Classical textual fragmentary heritage and the development of a collaborative environment for crowdsourced annotations. These goals are being achieved by implementing the Perseids Platform and by encoding the Fragmenta Historicorum Graecorum, one of the most important and comprehensive collections of fragmentary authors.